If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 186 = 2x Solving 186 = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 186 + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 186 + -2x = 0 Add '-186' to each side of the equation. 186 + -186 + -2x = 0 + -186 Combine like terms: 186 + -186 = 0 0 + -2x = 0 + -186 -2x = 0 + -186 Combine like terms: 0 + -186 = -186 -2x = -186 Divide each side by '-2'. x = 93 Simplifying x = 93
| X(5x+8)(7x-3)=0 | | -36x=-720 | | -70x=-560 | | 126=x+92 | | 2+6x=2+4x | | 26x=-78 | | -32x=96 | | -3x=108 | | -48x=96 | | -26x=104 | | c^2=-2c+45 | | x^2+2ax+a^2-9=0 | | -x=397 | | 41-7x=160 | | c^2=2c+16 | | 4(3x-1)=6(x-1) | | 23+x=19+11 | | 4x+3.75=x-6 | | Y=7/17 | | 11.3y=4052 | | (2y-5x-4)-(x-6y+5)= | | 38-4=8 | | 8(x)+10=-9 | | x+78=97 | | 8(x)+10=9 | | x-(-53)=-123 | | (-3x-y+2)+(-2x+4y-9)= | | x-(-62)=-54 | | -3(y+5)-21=0 | | 10+-18+15z+z= | | 3x-7/2=x/3 | | x-(-33)=-75 |